1995
DOI: 10.1142/s0218625x95000145
|View full text |Cite
|
Sign up to set email alerts
|

A PHOTOEMISSION STUDY OF THE ELECTRONIC STRUCTURE INDUCED BY POTASSIUM ADSORPTION ON TiO2(110)

Abstract: Electronic structure effects induced by potassium adsorption up to one monolayer (ML) on a nearly stoichiometric TiO 2(110) surface has been studied by means of angle-resolved photoemission spectroscopy (ARUPS and ARXPS) from valence states and core levels. In agreement with the observations on K/TiO 2(100) [P.J. Hardman et al., Surf. Sci.269/270, 677 (1992)], potassium adsorption at room temperature leads—due to K-to-substrate charge transfer—to the reduction of surface Ti ions (to nominally Ti 3+ ions), evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…This state is associated with a new peak in the electronic DOS about 1 eV above the VBM. States have been observed about 3 eV above the VBM in TiO 2 samples reduced by either adsorption of alkali metals [22][23][24][25]28,55 or by the creation of oxygen vacancies. 14,7,28 Spin-polarized states at a similar energy with respect to the VBM were found in recent theoretical investigations of potassium adsorption on the ͑110͒ surface 52 and on oxygen deficient ͑110͒ surfaces in which both DFT and HF approaches were used.…”
Section: B the Nature Of The Electronic Statementioning
confidence: 99%
See 2 more Smart Citations
“…This state is associated with a new peak in the electronic DOS about 1 eV above the VBM. States have been observed about 3 eV above the VBM in TiO 2 samples reduced by either adsorption of alkali metals [22][23][24][25]28,55 or by the creation of oxygen vacancies. 14,7,28 Spin-polarized states at a similar energy with respect to the VBM were found in recent theoretical investigations of potassium adsorption on the ͑110͒ surface 52 and on oxygen deficient ͑110͒ surfaces in which both DFT and HF approaches were used.…”
Section: B the Nature Of The Electronic Statementioning
confidence: 99%
“…1, [22][23][24][25][26][27][28] Low energy electron diffraction ͑LEED͒ data indicate that K adsorption on the ͑100͒ surface at half-monolayer coverage results in an ordered c(2ϫ2) geometry. 22 This is confirmed by surface x-ray absorption fine structure ͑SEXAFS͒ studies which also probe the local geometry of the adsorption site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stoichiometric surface has no occupied gap states and is inert to chemisorption of a wide variety of molecules , Both of them induce occupied gap states placed around 1 eV below the conduction band edge. Different spectroscopic evidences have shown that these states are predominantly Ti 3d in character. These results reveal the presence of reduced Ti atoms in the system.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that alkali metal adsorption induces a reduction of Ti 4+ to Ti 3+ on the surface through the electron transfer from the adsorbate (alkali metal ion) to Ti cations mediated by surface oxygen nally forming a surface layer in which adsorbate atoms are oxidized. [31][32][33][34][35][36] When more exposed oxygen sites are coupled with electrons from nitrogen doping, it is natural that the reaction energies and the corresponding potentials during ORR are decreased.…”
mentioning
confidence: 99%